Scavenging carbon deposition on alumina supported cobalt catalyst during renewable hydrogen-rich syngas production by methane dry reforming using artificial intelligence modeling technique - Alsaffar M.A.; Ayodele B.V.; Mustapa S.I. (Elsevier Ltd, 2023)
Alumina; Aluminum oxide; Carbon; Catalyst deactivation; Cobalt; Deposition; Forecasting; Greenhouse gases; Hydrogen production; Methane; Multilayer neural networks; Network architecture; Radial basis function networks; Statistical methods; Synthesis gas; Synthesis gas manufacture; Alumina-supported cobalt catalyst; Artificial neural network approach; Artificial neural network modeling; Methane dry reforming; Multi layer perceptron neural networks (MLPNN); Production of hydrogen; Radial basis functions; Syn-gas; Catalyst supports